Microbiomes and glyphosate biodegradation in edaphic and aquatic environments: recent issues and trends - Zabaloy, María Celina; Allegrini, Marco; Hernandez Guijarro, Keren; Behrends Kraemer, Felipe; Morras, Héctor José María; Erijman, Leonardo (Springer, 2022)
Glyphosate (N-(phosphonomethyl)glycine) has emerged as the top-selling herbicide worldwide because of its versatility in controlling annual and perennial weeds and the extensive use of glyphosate-resistant crops. Concerns related to the wide spread use of glyphosate and its ubiquitous presence in the environment has led to a large number of studies and reviews, which examined the toxicity and fate of glyphosate and its major metabolite, aminomethylphosphonic acid (AMPA) in the environment. Because the biological breakdown of glyphosate is most likely the main elimination process, the biodegra dation of glyphosate has also been the object of abundant experimental work. Importantly, glyphosate biodegradation in aquatic and soil ecosystems is afected not only by the composition and the activity of microbial communities, but also by the physical environment. However, the interplay between microbiomes and glyphosate biodegradation in edaphic and aquatic environments has rarely been considered before. The proposed minireview aims at flling this gap. We summarize the most recent work exploring glyphosate biodegradation in natural aquatic bioflms, the biological, chemical and physical factors and processes playing on the adsorption, transport and biodegradation of glyphosate at diferent levels of soil organization and under diferent agricultural managements, and its impact on soil microbial communities.